KAJIAN KARAKTERISTK GENETIK RUSA TIMOR (Cervus timorensis timorensis Blanville, 1822) - M Syamsul Arifin Zein; Bambang Surjobroto; Dedy D Solihin; Siti N Prijono (BERITA BIOLOGI, 1998)
A study on characteristic of genetic of the Timor deer (Cervus timorensis timorensis)was conducted during the periode of June - November 1997.Twenty four blood samples from Timor, Semau, Pantar, and Alor Island,Nusa Tenggara Timur Province were examined for this study.Restriction site analysis of part of ribosomeRNA mitochondrial DNA (447 bp),using restriction endonucleasis Haelll and Mbol showed that there were two haplotype variation.